2021
DOI: 10.1007/s00425-020-03519-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific leaf area is modulated by nitrogen via changes in primary metabolism and parenchymal thickness in pepper

Abstract: Main conclusion Nitrogen promotes changes in SLA through metabolism and anatomical traits in Capsicum plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
(86 reference statements)
0
5
0
4
Order By: Relevance
“…A presença de tricomas nas folhas pode levar a redução na perda de água pela transpiração, pois estas estruturas proporcionam um aumento da umidade do ar diretamente em contato com a superfície da folha, restringindo a perda de vapor de água dos estômatos para a atmosfera (Crang et al, 2018). Os tricomas também atuam na proteção contra a herbivoria e no aumento da refletância da radiação solar contribuindo na diminuição da temperatura da folha, evitando a saturação de enzimas (Evert, 2006;Raven et al, 2014;Lima 2021).…”
Section: Sclerolobium Paniculatumunclassified
See 2 more Smart Citations
“…A presença de tricomas nas folhas pode levar a redução na perda de água pela transpiração, pois estas estruturas proporcionam um aumento da umidade do ar diretamente em contato com a superfície da folha, restringindo a perda de vapor de água dos estômatos para a atmosfera (Crang et al, 2018). Os tricomas também atuam na proteção contra a herbivoria e no aumento da refletância da radiação solar contribuindo na diminuição da temperatura da folha, evitando a saturação de enzimas (Evert, 2006;Raven et al, 2014;Lima 2021).…”
Section: Sclerolobium Paniculatumunclassified
“…A presença de tecido esclerenquimático desenvolvido na nervura central é uma característica marcante em X. aromatica, o sistema vascular é totalmente circundado por uma bainha esclerenquimática fibrosa, o floema é disposto em um semi-arco descontínuo, separado por células esclerenquimáticas (Figura 5-A e E). Este tipo de esclerênquima fibroso é empregado, principalmente, na proteção do floema, e exerce como função secundária a sustentação estrutural das folhas (Crang et al, 2018;Rashid et al, 2021).…”
Section: Xylopia Aromaticaunclassified
See 1 more Smart Citation
“…SLA, which is a measure of thickness of the leaf, is a key trait explaining growth variations of plant species under different environments. N supply is an important factor that determines SLA (Koch et al, 1988;de Ávila Silva et al, 2021). It was reported that N-deficient wild radish plants had higher SLA compared with those grown under N-sufficient conditions (Koch et al, 1988).…”
Section: Productivity Of Shoot and Root And Leaf Growthmentioning
confidence: 99%
“…It was reported that N-deficient wild radish plants had higher SLA compared with those grown under N-sufficient conditions (Koch et al, 1988). In the study with pepper (Capsicum annuum), de Ávila Silva et al (2021) found that SLA decreased in response to increased N supply. In this study, compared with M. crystallinum grown with full N, 0 N plants had significantly lower SLA.…”
Section: Productivity Of Shoot and Root And Leaf Growthmentioning
confidence: 99%